2015
DOI: 10.1186/s13046-015-0130-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual-targeting of aberrant glucose metabolism in glioblastoma

Abstract: BackgroundGlioblastoma (GBM) is the most common and malignant primary brain tumor. In contrast to some other tumor types, aberrant glucose metabolism is an important component of GBM growth and chemoresistance. Recent studies of human orthotopic GBM in mice and in situ demonstrated GBM cells rely on both glycolysis and mitochondrial oxidation for glucose catabolism. These observations suggest that the homeostasis of energy metabolism of GBM cells might be further disturbed by dual-inhibition of glucose metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 55 publications
5
38
0
1
Order By: Relevance
“…We found that concurrent use of dichloroacetate with radiotherapy indeed prevented the increase in glycolytic rate observed following radiotherapy alone. Our previous study demonstrated that dichloroacetate effectively induced a dose-dependent proliferation arrest of in vitro cultures of glioblastoma cells but had no significant effect on noncancerous cells (15). This result is in line with most of the studies that investigated the efficacy of dichloroacetate demonstrating that a therapeutic window exists although suprapharmacologic level of dichloroacetate (5-50 mmol/L) is necessary to halt the growth of cancer cells in vitro (9,32,33,35).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We found that concurrent use of dichloroacetate with radiotherapy indeed prevented the increase in glycolytic rate observed following radiotherapy alone. Our previous study demonstrated that dichloroacetate effectively induced a dose-dependent proliferation arrest of in vitro cultures of glioblastoma cells but had no significant effect on noncancerous cells (15). This result is in line with most of the studies that investigated the efficacy of dichloroacetate demonstrating that a therapeutic window exists although suprapharmacologic level of dichloroacetate (5-50 mmol/L) is necessary to halt the growth of cancer cells in vitro (9,32,33,35).…”
Section: Discussionsupporting
confidence: 79%
“…Protein concentration was measured using BCA Assay Kit (Pierce). Proteins (50 mg/sample) were separated via reducing 10% SDS-PAGE, and standard Western blotting procedures (15) were used to detect proteins of interest with the following primary antibodies: g-H2AX (Cell Signaling Technology, CST #9718), HIF1a (CST, #3716), PDK-1 (CST, #3820), and b-actin (Abcam, ab8227). Images and densitometry were acquired by using ImageQuant TL software.…”
Section: Western Blottingmentioning
confidence: 99%
“…It is important to mention that all patents received standard of care therapy (Temozolomide and radiation) . DCA continues to be a promising anti‐cancer agent as a study showed that it sensitizes GBM cells to radiotherapy by inducing a G2‐M phase cell‐cycle arrest, reducing mitochondrial reserve capacity and increasing DNA damage …”
Section: Resultsmentioning
confidence: 99%
“…В работе [41] на клеточных линиях глиобласто-мы (U87, U251, LN229, DBTRG) изучалась эффек-тивность комбинированного применения НДХА и PENAO -мышьяксодержащего митохондриально-го токсина, подавляющего потребление кислорода и индуцирующего ОС и деполяризацию мембран митохондрий, приводя к запрограммированной клеточной гибели. НДХА, в свою очередь, пода-вляет гликолиз и продукцию кислот, вызванную PENAO, а также ингибирует экспрессию протеина MRP1, что ведет к увеличению накопления PENAO в цитозоле.…”
Section: опухоли нервной системыunclassified